A pilot study of the use of the oral and faecal microbiota for the diagnosis of ulcerative colitis and Crohn's disease in a paediatric population - Monleón-Getino, A.; Pujol-Muncunill, G.; Méndez Viera, J.; Álvarez Carnero, L.; Sanseverino, W.; Paytuví-Gallart, A.; Martín de Carpí, J. (Frontiers in Pediatrics, 2023)
Crohn's disease (CD) and ulcerative colitis (UC) are chronic inflammatory bowel diseases (IBD) that affect the gastrointestinal tract. Changes in the microbiome and its interaction with the immune system are thought to play a key role in their development. The aim of this study was to determine whether metagenomic analysis is a feasible non-invasive diagnostic tool for IBD in paediatric patients. A pilot study of oral and faecal microbiota was proposed with 36 paediatric patients divided in three cohorts (12 with CD, 12 with UC and 12 healthy controls [HC]) with 6 months of follow-up. Finally, 30 participants were included: 13 with CD, 11 with UC and 8 HC (6 dropped out during follow-up). Despite the small size of the study population, a differential pattern of microbial biodiversity was observed between IBD patients and the control group. Twenty-one bacterial species were selected in function of their discriminant accuracy, forming three sets of potential markers of IBD. Although IBD diagnosis requires comprehensive medical evaluation, the findings of this study show that faecal metagenomics or a reduced set of bacterial markers could be useful as a non-invasive tool for an easier and earlier diagnosis.